2013
DOI: 10.4269/ajtmh.12-0437
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Polymerase Chain Reaction for Detection of Strongyloides stercoralis in Stool

Abstract: Abstract. The use of real-time polymerase chain reaction (PCR) for detection of Strongyloides stercoralis in stool has recently been described. We compared five DNA extraction methods by using normal human stool spiked with Strongyloides ratti and tested by using a real-time PCR. The PowerSoil kit was found to be the best technique in terms of sensitivity and ease of use. The PCR detected DNA extracted from one spiked S. ratti larva diluted 10 −2 . The PowerSoil kit was then used to extract DNA from 160 human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 19 publications
2
71
0
4
Order By: Relevance
“…Whilst real-time PCR has shown very high specificity in human samples, it again has limited sensitivity, and has not proven to be diagnostically superior to other parasitologic techniques such as the Baermann method or APC [61,63,64•], particularly in low-density infections, supporting previous findings from animal models [65,66]. However, recent improvements of this technique may increase the sensitivity in the near future.…”
Section: Molecular Biologysupporting
confidence: 46%
“…Whilst real-time PCR has shown very high specificity in human samples, it again has limited sensitivity, and has not proven to be diagnostically superior to other parasitologic techniques such as the Baermann method or APC [61,63,64•], particularly in low-density infections, supporting previous findings from animal models [65,66]. However, recent improvements of this technique may increase the sensitivity in the near future.…”
Section: Molecular Biologysupporting
confidence: 46%
“…Analytical sensitivity and specificity are comparable to PCR, according to the method of Verweij et al 19,20,23 .…”
Section: Pcrmentioning
confidence: 99%
“…No PCR studies have reported false positive results when analytical specificity has been tested using DNA extracted from bacteria, viruses, fungi, protozoa, and other helminths 19,23,24,27,29,30 . Studies have also assessed the specificity of the PCR products by sequence analysis, with all finding 100% sequence homology with the target sequence of S. stercoralis.…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The DNA was extracted from S. ratti larvae in water and larvae spiked into normal human stool using a spin column method, the PowerSoil DNA Isolation Kit (Mo Bio Laboratories, Carlsbad CA), according to the manufacturer's instructions. 19 The DNA was extracted from a range of other parasites, fungi, and bacteria using standard methods (Table 1). These samples were either from pure cultures or, in the case of parasites, washed and concentrated organisms.…”
Section: Methodsmentioning
confidence: 99%